Driver reaction to navigation instructions incorporating good and poor landmarks - Tracy Ross; Andrew May; J.M. Duffield; S. Paszkowicz (2002)
The study consisted of a road-based trial involving 48 participants using a navigation system to complete a complex urban route. The participants were divided into three matched groups experiencing one of the following landmark conditions: good, poor or no landmarks, incorporated in verbal instructions. A range of objective and subjective measures were taken to assess driver performance with and attitudes to each of the landmark categories. The aims were to: • assess the impact on driver performance and attitudes of presenting navigation instructions which included good, poor or no landmarks • validate the REGIONAL model, which was developed to predict the navigational value of individual landmarks • identify any other factors (e.g. driver or manoeuvre characteristics) that may affect the value of landmarks